AvaR1, a Butenolide-Type Autoregulator Receptor in Streptomyces avermitilis, Directly Represses Avenolide and Avermectin Biosynthesis and Multiple Physiological Responses - Zhu, Jianya; Chen, Zhi; Li, Jilun; Wen, Ying (Frontiers in Microbiology, 2017)
Avermectins are commercially important anthelmintic antibiotics produced by Streptomyces avermitilis. The homologous TetR-family transcriptional regulators AvaR1 and AvaR2 in this species were identified previously as receptors of avenolide, a novel butenolide-type autoregulator signal required for triggering avermectin biosynthesis. AvaR2 was found to be an important pleiotropic regulator in repression of avermectin and avenolide production and cell growth, whereas the regulatory role of AvaR1 remains unclear. Investigation of AvaR1 function in the present study showed that it had no effect on cell growth or morphological differentiation, but inhibited avenolide and avermectin production mainly through direct repression of aco (the key enzyme gene for avenolide biosynthesis) and aveR (the cluster-situated activator gene). AvaR1 also directly repressed its own gene (avaR1) and two adjacent homologous genes (avaR2 and avaR3). Binding sites of AvaR1 on these five target promoter regions completely overlapped those of AvaR2, leading to the same consensus binding motif. However, AvaR1 and AvaR2 had both common and exclusive target genes, indicating that they cross-regulate diverse physiological processes. Ten novel identified AvaR1 targets are involved in primary metabolism, stress responses, ribosomal protein synthesis, and cyclic nucleotide degration, reflecting a pleiotropic role of AvaR1. Competitive EMSAs and GST pull-down assays showed that AvaR1 and AvaR2 competed for the same binding regions, and could form a heterodimer and homodimers, suggesting that AvaR1 and AvaR2 compete and cooperate to regulate their common target genes. These findings provide a more comprehensive picture of the cellular responses mediated by AvaR1 and AvaR2 regulatory networks in S. avermitilis.